Improving best‐phase image quality in cardiac CT by motion correction with MAM optimization. Issue 3 (8th February 2013) - Rohkohl, Christopher; Bruder, Herbert; Stierstorfer, Karl; Flohr, Thomas
Abstract : Purpose: : Research in image reconstruction for cardiac CT aims at using motion correction algorithms to improve the image quality of the coronary arteries. The key to those algorithms is motion estimation, which is currently based on 3‐D/3‐D registration to align the structures of interest in images acquired in multiple heart phases. The need for an extended scan data range covering several heart phases is critical in terms of radiation dose to the patient and limits the clinical potential of the method. Furthermore, literature reports only slight quality improvements of the motion corrected images when compared to the most quiet phase (best‐phase) that was actually used for motion estimation. In this paper a motion estimation algorithm is proposed which does not require an extended scan range but works with a short scan data interval, and which markedly improves the best‐phase image quality. Methods: : Motion estimation is based on the definition of motion artifact metrics (MAM) to quantify motion artifacts in a 3‐D reconstructed image volume. The authors use two different MAMs, entropy, and positivity. By adjusting the motion field parameters, the MAM of the resulting motion‐compensated reconstruction is optimized using a gradient descent procedure. In this way motion artifacts are minimized. For a fast and practical implementation, only analytical methods are used for motion estimation and compensation. Both the MAM‐optimization and a 3‐D/3‐D registration‐based motion estimation algorithm were investigated by means of a computer‐simulated vessel with a cardiac motion profile. Image quality was evaluated using normalized cross‐correlation (NCC) with the ground truth template and root‐mean‐square deviation (RMSD). Four coronary CT angiography patient cases were reconstructed to evaluate the clinical performance of the proposed method. Results: : For the MAM‐approach, the best‐phase image quality could be improved for all investigated heart phases, with a maximum improvement of the NCC value by 100% and of the RMSD value by 81%. The corresponding maximum improvements for the registration‐based approach were 20% and 40%. In phases with very rapid motion the registration‐based algorithm obtained better image quality, while the image quality of the MAM algorithm was superior in phases with less motion. The image quality improvement of the MAM optimization was visually confirmed for the different clinical cases. Conclusions: : The proposed method allows a software‐based best‐phase image quality improvement in coronary CT angiography. A short scan data interval at the target heart phase is sufficient, no additional scan data in other cardiac phases are required. The algorithm is therefore directly applicable to any standard cardiac CT acquisition protocol.